PEMANTAUAN MEAN ARTERIAL PRESSURE (MAP) PADA PASIEN SECTIO CAESAREA DENGAN MENGGUNAKAN TEKNIK ANESTESI SUB ARACHNOID BLOCK (SAB) DI RS PERTAMEDIKA UMMI ROSNATI BANDA ACEH - Mohammad Hendro Mustaqim; Eva Mardalena (Jurnal Sains Riset, 2021)
The aims of this research to obtain some information and to know whether there are significant inpact between giving anesthesia using Sub Arachnoid Block technique with the reduction of Mean Arterial Pressure for sectio caesarea patient. This research can be used as information to the public especially for clinicians, this research is also can be useful as reference and expand the knowlegde about given the anesthesia by Sub Arachnoid Block technique impact for sectio caesarea’s Mean Arterial Pressure patient. Analitical descriptive is used as method with cross sectional approach, and the data was collected by questioner assessment. The result of the study showed that Mean Arterial Pressure on sectio caesarea patients by using anesthesia Sub Arachnoid Block technique have been reduced, although it is not significant reductions.Keywords: Mean Arterial Pressure, Sub Arachnoid Block, Sectio Caesarea.